Discrete Dynamics by Different Concepts of Majorization - S. Sauerbrei; P. J. Plath; M. Eiswirth (International Journal of Mathematics and Mathematical Sciences)
For the description of complex dynamics of open systems, an approach is given by different concepts of majorization (order structure). Discrete diffusion processes with both invariant object number and sink or source can be represented by the development of Young diagrams on lattices. As an experimental example, we investigated foam decay, dominated by sinks. The relevance of order structures for the characterization of certain processes is discussed.